Analisis Faktor-Faktor yang Mempengaruhi Tingkat Kesiapan Era Industri 4.0 di Masa Pandemi COVID-19 pada Pegawai di DKI Jakarta: The Analysis of Factors Affecting Preparation Level for the Industry 4.0 Era in the COVID-19 Pandemic on Employees in DKI Jakarta - Rianti Setiadi; Franky Franky (Society, 2021)
This study analyses significant factors affecting the level of preparation for the industry 4.0 era related to anxiety about the COVID-19 pandemic on employees in DKI Jakarta. Apart from being influenced by the anxiety of the COVID-19 pandemic, the level of preparation for the industry 4.0 is also differentiated by gender, age, education, marital status, decreasing income, and loyalty. Therefore, companies can arrange the planning related to preparing the industry 4.0 during the COVID-19 pandemic if those factors have been figured out. This study used a quantitative method, and the population of this study is full-time employees in DKI Jakarta. The sample was selected by using the snowball sampling technique distributed to 12 companies in DKI Jakarta. The distribution was conducted through the WhatsApp application for a month, and it was gained 228 respondents. Snowball sampling technique used in correlation with the implementation of large-scale social restrictions caused by COVID-19 pandemic. The data analysis used a multiple linear regression model. The results show that factors affecting the level of employees’ preparation in DKI Jakarta for industry 4.0 related to the anxiety of the COVID-19 pandemic are loyalty and a decrease in income.